Drinding technology of silicon metal - Nusupbekov, B.R.; Khassenov, A.K.; Beisenbek, A.Zh. (Publishing House of the KarSU named after E.A.Buketov, 2012)
In article is presented application silicon, and advantage him(it) in contrast with the other semiconductor. The aims and purposes of processing of metallurgical silicon electrohydraulic way. Proposed optimal processing parameters of the product. The Certain admixture other element in composition metallurgical silicon processed электрогидравлическим way, and got given are compared to product reduced in mechanical grinder. Processing metallurgical silicon on электрогидравлическим installation does not require the greater expenses for reception powder silicon in necessary proportion
Keywords: electro-technology; metallurgical silicon